Customer relationship management in banking industry: Modern approach - Cvijović, Jelena; Kostić-Stanković, Milica; Reljić, Marija (Industrija, 2017)
Due to fierce competition in the banking sector, where the competitive struggle to win larger market share and attract the largest possible number of customers is constantly being led, and taking into account poorly differentiated offer of banks, adequate customer relationship management is a fundamental tool for achieving better business results. In this context, the subject of the paper is the identification of the characteristics of the modern approach to customer relationship management and factors that influence its successful implementation, in order to achieve long-term and mutually beneficial relations between banks and banking products and services users.
Keywords: Customer satisfaction; Customer trust; Segmentation; Banking industry; Management; Industries; Customers; Customer relationship management; Banking